92.1k views
1 vote
Show all your work to receive full credit for this problem. Solve the system of equations using the elimination method. 2a + 3b = -1 3a + 5b = -2

1 Answer

1 vote

Given equations are;
2a + 3b = -1 ..................equation 1
3a + 5b = -2 ....................equation 2

Now multiply equation 1 with (-3)

The equation will be;

-6a -9b = 3 …………………..equation 3

Now multiply equation 2 with (2)

The equation will be;

6a + 10b = -4 ……………..equation 4

Now add equation 3 and equation 4

-6a – 9b = 3

6a + 10b = -4

------------------------------

0a + b = -1

b = -1

Now put the value of b in equation 1

2a + 3(-1) = -1

2a -3 = -1

2a = -1+3

2a = 2

a=1

Thus the solution is (a,b) = (1,-1)


User Lascoff
by
5.5k points